2020
DOI: 10.1371/journal.pone.0234851
|View full text |Cite
|
Sign up to set email alerts
|

A scalable method of applying heat and humidity for decontamination of N95 respirators during the COVID-19 crisis

Abstract: A lack of N95 Filtering Facepiece Respirators (FFRs) during the COVID-19 crisis has placed healthcare workers at risk. It is important for any N95 reuse strategy to determine the effects that proposed protocols would have on the physical functioning of the mask, as well as the practical aspects of implementation. Here we propose and implement a method of heating N95 respirators with moisture (85˚C, 60-85% humidity). We test both mask filtration efficiency and fit to validate this process. Our tests focus on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 15 publications
2
79
0
Order By: Relevance
“…The possibility that disposable N95 masks could be sterilized and reused was raised 15 years ago as a strategy to address shortages arising from medical emergencies 3 – 5 , but following an FDA-funded study by the Battelle Memorial Institute 6 , relatively little subsequent research has been performed on the topic 7 9 . Recently, in response to acute N95 mask shortages, multiple strategies for mask sterilization have been proposed and studied, including exposure to ultraviolet (UV) germicidal irradiation, vaporized hydrogen peroxide, moist heat, ethylene oxide, and gamma irradiation 7 13 . In this study, we evaluate a recently developed technology, ionized hydrogen peroxide (iHP), as a method for sterilizing N95 masks and other PPE.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that disposable N95 masks could be sterilized and reused was raised 15 years ago as a strategy to address shortages arising from medical emergencies 3 – 5 , but following an FDA-funded study by the Battelle Memorial Institute 6 , relatively little subsequent research has been performed on the topic 7 9 . Recently, in response to acute N95 mask shortages, multiple strategies for mask sterilization have been proposed and studied, including exposure to ultraviolet (UV) germicidal irradiation, vaporized hydrogen peroxide, moist heat, ethylene oxide, and gamma irradiation 7 13 . In this study, we evaluate a recently developed technology, ionized hydrogen peroxide (iHP), as a method for sterilizing N95 masks and other PPE.…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies 24,26,27,33,37,42,48,49,62 evaluated the effect of moist heat between 60 and 100°C. The method did not alter mask t, odor or comfort.…”
Section: Moist Heat / Pasteurizationmentioning
confidence: 99%
“…2006). Since that time, research has been conducted on a variety of decontamination methods, including physical and chemical options, to extend the supply until additional supplies become available (Viscusi et al 2009;Bergman et al 2010;Fisher et al 2011;Heimbuch et al 2011;Viscusi et al 2011;Lore et al 2012;Heimbuch et al 2014;Lin et al 2018;Mills et al 2018;Anderegg et al 2020;Cadnum et al 2020;Fischer et al 2020;Grinshpun et al 2020;Jatta et al 2020;Li et al 2020;Ma et al 2020;Pauley et al 2020;Schnell et al 2020;Widmer and Richner 2020;Xiang et al 2020;Zulauf et al 2020). Moist heat is one of the methods that was shown to reduce the amount of infectious MS2 phage (Fisher et al 2011;Li et al 2020;Zulauf et al 2020), methicillin-resistant Staphylococcus aureus (MRSA) (Li et al 2020), influenza virus (Heimbuch et al 2011;Lore et al 2012) and avian infectious bronchitis virus (Ma et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other research on the stability of SARS-CoV-2 on surfaces and in aerosols has shown that the virus loses viability quicker at higher temperatures and relative humidity conditions (Aboubakr et al 2020;Biryukov et al 2020;Schuit et al 2020), suggesting that this approach will be effective for decontamination of FFRs contaminated with SARS-CoV-2. It has also been shown that moist heat often does not degrade FFR performance for collection efficiency and inhalation resistance (Bergman et al 2010;Fisher et al 2011;Viscusi et al 2011;Lore et al 2012;Anderegg et al 2020;Zulauf et al, 2020), though some moist heat conditions have impacted FFR fit or the adhesion of the foam nose pad on certain FFR models (Bergman et al 2010;Viscusi et al 2011;Lore et al 2012). Consistent with these studies, the U.S. Food and Drug Administration (FDA) issued an Emergency Use Authorization (EUA) for moist heat as described in the Steris Steam Decon Cycle in AMSCO Medium Steam Sterilizers (Hinton 2020), and 3M issued a technical bulletin stating that moist heat was an acceptable method for select FFR models (Anon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation